A Reconciliation for the Future of Psychiatry: Both Folk Psychology and Cognitive Science - Hutto, Daniel D. (Frontiers in Psychiatry, 2016)
Philosophy of psychiatry faces a tough choice between two competing ways of understanding mental disorders. The folk psychology or FP view puts our everyday normative conceptual scheme in the driver’s seat – on the assumption that it, and it only, tells us what mental disorders are (Graham 2009). Opposing this, the scientific image or SI view (Murphy 2006, Gerrans 2014) holds that our understanding of mental disorders must come, wholly and solely, from the sciences of the mind, unfettered by FP. This paper argues that the FP view is problematic because it is too limited: there is more to the mind than FP allows, hence we must look beyond FP for properly deep and illuminating explanations of mental disorders. SI promises just this. But when cast in its standard cognitivist formulations SI is unnecessarily and unjustifiably neurocentric. After rejecting both the FP view, in its pure form, and SI, in its popular cognitivist renderings, this paper concludes that a more liberal version of SI can accommodate what is best in both views – once SI is so formulated and the FP view properly edited and significantly revised, the two views can be reconciled and combined to provide a sound philosophical basis for a future psychiatry.